A nationwide genetic analysis of inherited retinal diseases in Israel as assessed by the Israeli inherited retinal disease consortium (IIRDC). Issue 1 (15th September 2019) - Sharon, Dror; Ben‐Yosef, Tamar; Goldenberg‐Cohen, Nitza; Pras, Eran; Gradstein, Libe; Soudry, Shiri; Mezer, Eedy; Zur, Dinah; Abbasi, Anan H.; Zeitz, Christina; Cremers, Frans P. M.; Khan, Muhammad I.; et al.
Abstract: Inherited retinal diseases (IRDs) cause visual loss due to dysfunction or progressive degeneration of photoreceptors. These diseases show marked phenotypic and genetic heterogeneity. The Israeli IRD consortium (IIRDC) was established in 2013 with the goal of performing clinical and genetic mapping of the majority of Israeli IRD patients. To date, we recruited 2, 420 families including 3, 413 individuals with IRDs. On the basis of our estimation, these patients represent approximately 40% of Israeli IRD patients. To the best of our knowledge, this is, by far, the largest reported IRD cohort, and one of the first studies addressing the genetic analysis of IRD patients on a nationwide scale. The most common inheritance pattern in our cohort is autosomal recessive (60% of families). The most common retinal phenotype is retinitis pigmentosa (43%), followed by Stargardt disease and cone/cone–rod dystrophy. We identified the cause of disease in 56% of the families. Overall, 605 distinct mutations were identified, of which 12% represent prevalent founder mutations. The most frequently mutated genes were ABCA4, USH2A, FAM161A, CNGA3, and EYS . The results of this study have important implications for molecular diagnosis, genetic screening, and counseling, as well as for the development of new therapeutic strategies for retinal diseases.